Reflective Style and Speech Production During Academic Task Solving In University Students - Savchenko, Olena; Kalmykov, Heorhii; Malimon, Liudmyla (East European Journal of Psycholinguistics, 2020)
The aim of the article is to examine the relationship between students’ reflective information processing style and speech production during academic tasks solving. The study applies Index of Learning Styles Questionnaire (Felder & Solomon, 2001) to examine four pairs of learning styles, notably active –reflective, sensing – intuitive, visual – verbal and sequential - global. The study applies functional analysis suggested by Naydonov (2008). The students were asked to solve the academic tasks aligned with their knowledge of the academic module. The study applies analysis of fourteen categories according to the following two criteria, notably considering the content/meaning of students’ responses and type of solution. The findings indicate that students with a high level of reflective and verbal style less frequently apply category text (34.55±12.39), comparatively with students with a low level of reflective та verbal style (65.94±4.13). Students with a high level of reflective and verbal style more frequently apply category tools (6.61±1.96) and less frequently category intentions (1.69±1.78) comparatively with students with a low level of reflective and verbal style (1.06±.78 and 2.30±.71, respectively). Category models are more frequent in students with a medium level of reflective style (3.61±.99), comparatively with students with a high (2.05±2.76) and a low (2.69±1.01) level. Therefore, speech production in categories of models and tools evaluates the best solutions in the academic setting, providing an efficient academic task solving.